Donald Winnicott today - Abram, Jan., ....- (London : Routledge, 2013)
What in Winnicott's theoretical matrix was truly revolutionary for psychoanalysis? In this book, the editor and contributors provide a rare in-depth analysis of his original work, and highlight the specifics of his contribution to the concept of early psychic development which revolutionised the theory and practice of psychoanalysis. Including re-publications of selected Winnicott papers to set the scene for the themes and explorations in subsequent chapters, the book examines how Winnicott expanded Freud's work, and how his discourse with Melanie Klein sharpened his thought and clinical innovations. Divided into 3 sections, it covers: •Introductory overviews on the evolution of Winnicott's theoretical matrix •Personal perspectives from eminent psychoanalysts on how Winnicott's originality inspired their own work •Further recent examinations and extensions including new findings from the archives Drawing on her own extensive knowledge of Winnicott and the expertise of the distinguished contributors, Jan Abram shows us how Winnicott's contribution constitutes a major psychoanalytic advance to the concept of subjectivity. As such, it will be an inspiration to experienced psychoanalysts, psychotherapists and all those interested in human nature and emotional development.
Introduction. Part I: Introductory Overviews. Winnicott, D.W.W. On D.W.W. Ogden, The Mother, the Infant and the Matrix: Interpretations of Aspects of the Work of Donald Winnicott. Abram, The Evolution of Winnicott's Theoretical Matrix: A Brief Outline. Loparic, From Freud to Winnicott: Aspects of A Paradigm Change. Part II: Personal Perspectives. Winnicott, A Personal View of the Kleinian Contribution. Milner, Winnicott: Overlapping Circles and the Two Way Journey. Green, Potential Space In Psychoanalysis: The Object In the Setting. Faimberg, Nachträglichkeit and Winnicott's Fear of Breakdown. Ogden, Reading Winnicott. Widlöcher, Winnicott and the Acquisition of Freedom of Thought. Wright, The Search For Form: A Winnicottian Theory of Artistic Creation. Roussillon,Winnicott's Deconstruction of Primary Narcissism. Part III: Late Winnicott Studies. Winnicott, The Use of An Object In the Context of ‘Moses and Monotheism'. Abram, D.W.W.'S Notes For the Vienna Congress 1971: A Consideration of Winnicott's Theory of Aggression and An Interpretation of the Clinical Implications. Goldman, Vital Sparks and the Form of Things Unknown. Reeves, On the Margins: The Role of the Father In Winnicott's Writings. Thompson, Winnicott and American Psychoanalysts. Farley, Squiggle Evidence: The Child, the Canvas, and the ‘Negative Labour' of Writing History.
Includes bibliographical references and index.
Keywords: Winnicott, D. W. -- 1896-1971.; Psychoanalyse; Psychoanalysis